2023
DOI: 10.1002/mabi.202300316
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of Cell‐Adhesive Proteins in 3D‐Printed Lipoic Acid‐Maleic Acid‐Poly(Propylene Glycol)‐Based Tough Gel Ink for Cell‐Supportive Microenvironment

Hao Nguyen Tran,
In Gul Kim,
Jong Heon Kim
et al.

Abstract: In extrusion‐based 3D printing, the use of synthetic polymeric hydrogels can facilitate fabrication of cellularized and implanted scaffolds with sufficient mechanical properties to maintain the structural integrity and physical stress within the in vivo conditions. However, synthetic hydrogels face challenges due to their poor properties of cellular adhesion, bioactivity, and bio‐functionality. In the past few years, new compositions of hydrogel inks have been designed to address this limitation. We recently d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…This results in hydrogels with superior mechanical, functional and biocompatible properties compared to pure gelatin hydrogels. Also, gelatin can be combined with synthetic polymers to improve the ink's properties, because usually synthetic polymers lack bioactive properties but have high mechanical characteristics [44]. The gelatin-based hydrogel can be crosslinked with a combination of tannic acid and ferrous sulfate to achieve better extrudable and stable properties for 3D bioprinting [45].…”
Section: Hydrogels Used With Calcium Phosphates In 3d Bioprintingmentioning
confidence: 99%
“…This results in hydrogels with superior mechanical, functional and biocompatible properties compared to pure gelatin hydrogels. Also, gelatin can be combined with synthetic polymers to improve the ink's properties, because usually synthetic polymers lack bioactive properties but have high mechanical characteristics [44]. The gelatin-based hydrogel can be crosslinked with a combination of tannic acid and ferrous sulfate to achieve better extrudable and stable properties for 3D bioprinting [45].…”
Section: Hydrogels Used With Calcium Phosphates In 3d Bioprintingmentioning
confidence: 99%
“…7). 32 In in vivo studies, four weeks after implantation in mice, protein-loaded scaffolds showed great biocompatibility and increased angiogenesis without an inflammatory response, demonstrating the promise as a printable tough hydrogel ink for tissue engineering.…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…Consequently, these have been extensively studied in biomedical applications, including protein modification, 25,26 tumor treatment, 27,28 biosensing, 29–31 and tissue scaffold 3D-printing. 32 Most reviews 33,34 have primarily focused on the properties and clinical applications of small-molecule LA, while limited attention is given to the synthesis strategies and biological applications of PLA-based systems. In this work, after fully considering the impact of specific structures on biological performances, we highlight the latest advancements of PLA in polymerization methods and biomedical applications, and the prospects for further development in the future (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%